2022
DOI: 10.1007/s11356-022-22492-0
|View full text |Cite
|
Sign up to set email alerts
|

Do green bonds offer a diversification opportunity during COVID-19?—an empirical evidence from energy, crypto, and carbon markets

Abstract: The present study is a novel attempt to unravel the connectedness of the green bond with energy, crypto, and carbon markets using the S&P green bond index (RSPGB). We consider MAC global solar energy index (RMGS) and ISE global wind energy index (RIGW) as proxies of the energy market and use bitcoin and the European energy exchange carbon index (REEX) for the cryptocurrency and carbon market. Employing the Diebold and Yilmaz (2012), Baruník and Krehlík (2018), and wavelet coherence econometric techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Similarly, the study conducted by [50][51][52][53][54] contributed to understanding the connectivity, risk transmission, and portfolio implications of green bonds, carbon pricing, and renewable energy stocks, among others. They highlight the importance of considering socially responsible investment practices, the potential of green bonds as hedging and diversification instruments, and the role of these assets in the global financial recovery and transition to a low-carbon economy.…”
Section: Trunkmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the study conducted by [50][51][52][53][54] contributed to understanding the connectivity, risk transmission, and portfolio implications of green bonds, carbon pricing, and renewable energy stocks, among others. They highlight the importance of considering socially responsible investment practices, the potential of green bonds as hedging and diversification instruments, and the role of these assets in the global financial recovery and transition to a low-carbon economy.…”
Section: Trunkmentioning
confidence: 99%
“…Figure 11 presents the most frequent keywords, including authors' keywords and KeyWords Plus, from 2016 to 2023 (June). Analyzing authors' keywords provides valuable insights into research trends from the researchers' perspective [53]. On the other hand, KeyWords Plus are terms extracted from titles or abstracts [36].…”
Section: Most Frequent Abstractmentioning
confidence: 99%
“…Their findings indicate that market-wide herding behavior prevails in falling markets for both liquid and illiquid periods. Yadav et al. (2023) study the potential diversification prospects between the green bonds and the markets of energy, crypto, and carbon using indexes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brammer & Bennett (2022) suggested that land managers use the growing carbon credits for taking advantage of carbon markets. Yadav et al (2022) concluded the short-run diversification opportunity among green bonds, energy stock, bitcoin, and the carbon market.…”
Section: Introductionmentioning
confidence: 99%